At a crossroads: consequential trends in recognition of community-based forest tenure from 2002-2017. Issue 2 (3rd May 2020) - Ginsburg, Chloe; Keene, Stephanie
ABSTRACT: Insecure, contested, and unjust forest tenure arrangements undermine forest investment and protection, fuel conflict, and jeopardize Indigenous Peoples', local communities', and indigenous and community women's rights, livelihoods, and development prospects. While legally recognized community forests tend to have lower rates of deforestation, store more carbon and benefit more people than forests managed by either public or private entities, evidence shows over two-thirds of forests remain controlled by governments – a significant portion of which is contested by indigenous and local communities who traditionally own, manage, and depend on these forests. It is therefore all the more critical that governments support and advance communities' forest tenure rights. Using longitudinal tenure data and analysis of global forest ownership trends developed by the Rights and Resources Initiative, this article details the distribution of statutory forest rights across 58 countries covering nearly 92% of global forests over the fifteen-year period from 2002–2017.